Value-Based Performance Excellence Model For Higher Education Institutions - M. R., Abdul Hamid (Springer Netherlands, 2014)
Organisational performance measurement method has shifted from measuring not only the tangibles aspect but also the intangibles aspects. Tangible aspects cover financial factors such as return on capital, cash flow and profitability, while the intangible aspects are related to non-financial factors such as the organisational core values. Therefore, this article aimed to test the performance excellence model based on core values indicators. This excellence model consists of six value-based performance criteria, which are leadership, culture, productivity-focused, employee-focused, stakeholder-focused and overall performance. Each criterion is measured using six core values of performance indicators. A total of 12 hypotheses have been put forward to test the relationships amongst the six criteria of excellence in the model. The model is analysed using structural equation modeling with AMOS software version 18.0 using maximum likelihood estimation. The questionnaire was developed and distributed to the respondents in Higher Education Institutions (HEIs) in Malaysia; out of 1,100 questionnaires distributed, 537 questionnaires were returned. The results of the modeling analysis revealed that the fit statistics of value-based performance excellence model for HEI is admissible. From the results, it is found that the leadership values have significant impact on the university culture values, employee values and the stakeholder values. Similarly, the culture values significantly affect the productivity values and employee values. Furthermore, employee values have significant influence on the productivity and stakeholder values. In addition, the productivity and stakeholder values significantly influence the university performance. However, the results of the study also found that there is no significant relationship between the leadership values and the productivity values, and between the culture values and the stakeholder values in the university settings. Furthermore, the relationship between the employee values towards university performance is found to be insignificant. From the study, it can be concluded that the relationships that are statistically significant and practically important should be given a due attention by the authorities in order to enhance the performance of the university through value-based indicators.